2019
DOI: 10.3390/e21010050
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Element Bearing Fault Diagnosis under Impulsive Noise Environment Based on Cyclic Correntropy Spectrum

Abstract: Rolling element bearings are widely used in various industrial machines. Fault diagnosis of rolling element bearings is a necessary tool to prevent any unexpected accidents and improve industrial efficiency. Although proved to be a powerful method in detecting the resonance band excited by faults, the spectral kurtosis (SK) exposes an obvious weakness in the case of impulsive background noise. To well process the bearing fault signal in the presence of impulsive noise, this paper proposes a fault diagnosis met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In the classical approach of cyclostationary-based techniques the assumption of Gaussian noise is taken under consideration [7,9,[22][23][24][25][26]. However, one can find the papers where the algorithms for the signals with non-Gaussian noise are proposed [27][28][29][30][31][32][33][34][35][36][37][38]. We refer also to the recent paper, where the new definition of the cyclostationary non-Gaussian signal is given, see [27] for more details.…”
Section: Introductionmentioning
confidence: 99%
“…In the classical approach of cyclostationary-based techniques the assumption of Gaussian noise is taken under consideration [7,9,[22][23][24][25][26]. However, one can find the papers where the algorithms for the signals with non-Gaussian noise are proposed [27][28][29][30][31][32][33][34][35][36][37][38]. We refer also to the recent paper, where the new definition of the cyclostationary non-Gaussian signal is given, see [27] for more details.…”
Section: Introductionmentioning
confidence: 99%
“…Rolling bearings are a crucial part in modern industrial manufacture, which can be found in linear guides, precision machine tools, and engine parts, etc., whose failure may result in serious safety accidents and economic loss. Therefore, one of the major topics to be investigated in preventing failures of mechanical systems is recognizing and diagnosing rolling bearing faults [1,2]. Unfortunately, rolling bearings are prone to failure to some extent because of complex operating conditions and structural characteristics [3].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that all the time series are mapped to the same dispersion pattern, although their trends are different. Meanwhile, the time series are mapped by the proposed FSDE, factor f is added as an additional element to the end of the class sequence, the new class sequences are[4,4,4,4, 0],[4,4,4,4, 1], and[4,4,4,4,2]. In the example, the time series originally mapped to the same dispersion pattern are finely mapped to more dispersion patterns.Figure 2illustrates the way that f is added to the sequence ,…”
mentioning
confidence: 99%
“…Impulsive control problems are well described by impulsive differential systems. Due to their numerous applications in various fields, such as engineering [1][2][3], biotechnologies and ecosystems management [4], chemical kinetics [5], and finance and investment [6,7], such systems have been extensively studied in past years. See, for example, [8,9] and the references therein for some fundamental results on impulsive differential equations and related impulsive control models.…”
Section: Introductionmentioning
confidence: 99%